Subjective and Objective Quality Assessment for Volumetric Video - Zermin, Emin; Smolic, Aljosa (Elsevier, 2022)
Volumetric video (VV) is a novel formof video that allows recreation of real-world scenes in 3D with users consuming the content from any viewpoint they desire. This makes VV best suited for augmented reality (AR) or virtual reality (VR) applications. This freedom necessitates increased user interaction with the VV itself, which brings new challenges to its visual quality assessment. In this chapter, various aspects of VV quality assessment using subjective user studies and objective quality estimation methods are discussed. These aspects include the way or representing 3D models, mode of interaction, display settings (e.g., whether AR or VR headsets are used), rendering parameters, and how the characteristics of point clouds or meshes are used in quality estimation. The chapter discusses the advantages and disadvantages of different methods and provides take away messages for researchers.
Keywords: Subjective quality assessment; Objective quality metrics; Point cloud; Mesh; Datasets; User interaction; Perception